The Accountability of Public Services during Covid-19 Pandemic in Bone Regency, South Sulawesi Province - Murtir Jeddawi; Riana Riana; Andi Sutra Rimba; Jamaruddin Suro (Lembaga Sembilan Tiga Community, 2022)
This study discusses the accountability of public services during the Covid-19 pandemic at the Tanete Riattang district office, Bone Regency, South Sulawesi Province. The objectives of this research are, first, to find out the types of licensing and non-licensing administrative services needed by the community, and second objective is how the accountability of public service procedures during the Covid-19 pandemic. the method used was a qualitative method with a case study approach, where data collection techniques are through interviews, documentation, and observations. The informants are the district head, the district secretary, the head of the public service section, the head of the public orderliness and peace section and the staff of the Tanete Riattang district. The results of the research showed that licensing and non-licensing administrative services during the covid-19 pandemic are going well. The community was obliged to comply with health protocols, even though the number's services were increasing compared to before covid-19. The service system used Standard Operating Procedures (SOP) without service fees and employees apply moral values, namely